LANGUAGE MAINTENANCE OF MINANG FAMILY IN BANDUNG:A Case Study of Two Minang Families - Merisa Putri, - (2011)
The aim of this study was to discover language maintenance of Minang people after considering the good existence of Minang people in such multilingual city at Bandung. A case study was employed to describe language maintenance of Minang people through their language use in low domains namely family, neighbourhood, and friendship domain and their attitude to Minang language. Questionnaire, interview and observation were employed to collect the data concerning those matters. The data from the questionnaire were analyzed by using simple statistic. Moreover, the data from the interview and observation were analyzed qualitatively by reading the transcription, color coding, and sense making. From this study it was discovered that the mostly language use of Minang family in low domain was Bahasa Indonesia. While the Minang language use was only used in extended family and as mixing languages in some domains. In term of language attitude, members of the first family have positive attitude to Minang language and it is only parents of second family have positive attitude. However, there is no deliberate attempts which are found in both families since these families perceive Minang language as a part of culture not to a tool for communication. Therefore, parents just introduce Minang language to their children without support them to use it.